Learning environment and attitudes among mathematics students with specific learning disabilities in self-contained and inclusion classes - Thomas-Bell, Christine Gennis (Curtin University, 2015)
I investigated attitudes and classroom environments among 242 eight-grade students with specific learning disabilities in inclusion classes, general-education students in inclusion classes, and students with specific learning disabilities in self-contained classes in Florida. Students with specific learning disabilities in integrated settings had higher scores than students with disabilities in separate settings, especially for task orientation and enjoyment. In integrated classes, general-education student had higher scores than students with specific learning disabilities.